Sub-Inhibitory Antibiotic Exposure and Virulence in Pseudomonas aeruginosa - Charlotte Nolan; Volker Behrends (MDPI AG, 2021)
Pseudomonas aeruginosa is a prime opportunistic pathogen, one of the most important causes of hospital-acquired infections and the major cause of morbidity and mortality in cystic fibrosis lung infections. One reason for the bacterium's pathogenic success is the large array of virulence factors that it can employ. Another is its high degree of intrinsic and acquired resistance to antibiotics. In this review, we first summarise the current knowledge about the regulation of virulence factor expression and production. We then look at the impact of sub-MIC antibiotic exposure and find that the virulence-antibiotic interaction for P. aeruginosa is antibiotic-specific, multifaceted, and complex. Most studies undertaken to date have been in vitro assays in batch culture systems, involving short-term (<24 h) antibiotic exposure. Therefore, we discuss the importance of long-term, in vivo-mimicking models for future work, particularly highlighting the need to account for bacterial physiology, which by extension governs both virulence factor expression and antibiotic tolerance/resistance.